High-quality reports and their characteristics in the Japanese Adverse Drug Event Report database (JADER) - Masami Tsuchiya; Taku Obara; Makoto Miyazaki; Aoi Noda; Takamasa Sakai; Ryohkan Funakoshi; Nariyasu Mano (Journal of Pharmacy & Pharmaceutical Sciences, 2021)
Purpose: Spontaneous adverse drug reaction reporting is the foundation of postmarketing drug safety monitoring. The present study aimed to analyze and clarify the quality and characteristics of the Japanese Adverse Drug Event Report database (JADER) using the World Health Organization (WHO) documentation grading scheme and the vigiGrade completeness score. The characteristics of reports were described using both schemes simultaneously. The way of proper use of these two schemes was explored. Methods: The WHO documentation grading scheme and the vigiGrade completeness score were applied to the same dataset (JADER202001 dataset). Reports classified as high-quality under both assessment criteria were extracted, and the characteristics of these reports were analyzed. Results: Of the 607,361 adverse drug reaction reports analyzed, 52.8% were ‘well-documented reports’ with a vigiGrade completeness score >0.8. Under the WHO documentation grading scheme, 328,702 reports (54.1%) were Grade 2 and 5,178 (0.9%) were Grade 3 (including rechallenge information). Among well-documented Grade 3 reports, classified as the highest quality, a high proportion of the adverse drug reaction reports were related to disorders of hematopoietic function resulting from anticancer drugs. Because a high proportion of the reports with rechallenge information were for anticancer drugs as suspect drugs, the WHO documentation grading scheme tended to extract reports regarding anticancer drugs as high quality. Conclusions: We conclude that the two schemes need to be used appropriately, depending on the purpose of analysis, the target adverse drug reactions, and suspect drugs.